Does Skill Performance Influence Young Children's Perceived Physical Competence?. Issue 5 (October 2022) - Johnson, Jerraco L.; Wadsworth, Danielle D.; Rudisill, Mary E.; Irwin, Jacqueline M.; Bridges, Claire
Children's self-perceived competence is critical for their engagement in fundamental motor skills (FMS), although these perceptions are highly inaccurate until around age seven (grade 2). Moreover, FMS competence is highly correlated with physical activity engagement in childhood. In this study we examined: (a) if children's perceptions of their FMS competence differed after they were allowed to perform the skill or observe their performance, and (b) if the accuracy of children's perceived competence changed under those conditions. Child participants ( N = 76; K-second grade) judged their own competence for three physical skills (running, skipping and dribble or hopping) on the Harter and Pike Pictorial Scale of Perceived Competence and Social Acceptance under three conditions: (a) a no-performance baseline, (b) after performing each skill, and (c) after observing themselves performing the skill. A repeated measures analysis of variance (ANOVA) indicated that their perceived competence differed across these conditions for running but not for skipping/hopping ( p = .556) or for dribbling ( p = .368). Spearman's rho correlations showed that their perceived running competence scores better predicted their actual competence after observing their performance ( rs = .25, p = .029) than after other conditions. Both performing and observing their performance were associated with changes in perceptions of running competence. Future research should focus on how and when children's perceived competence is assessed and how perceptions relate to FMS and physical activity engagement.